HAK – HAK TERSANGKA PADA TINGKAT PENYELIDIKAN DAN PENYIDIKAN DALAM PROSES PERKARA PIDANA DI POLTABES SAMARINDA - Endi Sri Prabowo (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT Suspect dealing with the public prosecutor before the courts, both have the same position as well as the rights they have. Prosecutors will try to provide evidence to the court that can convince a judge that the suspect guilty and deserve to get a penalty. Prosecutors will try to show the items of evidence relating to misconduct in the case that alleged the suspects. Even the public prosecutor can bring witnesses who can incriminate a suspect. While the suspect himself entitled to deny what has been alleged by showing the evidence, even what he has alleged is not true. The suspect also can bring witnesses who can relieve it (witness a de charge). If the suspect was able to prove that he is innocent, then the interrogation of suspects and defendants discontinued immediately free of any charges that have been attributed to him. If the suspect can not prove that he is innocent, then the criminal proceedings against the suspects will be forwarded to the final stage. If there has been a violation of his rights by investigators, the suspect can do something that can make the investigator in question must be accountable for his actions. Legal remedies that may be filed by the suspect, his family and his lawyers are pre-trial efforts. With this pre-trial, suspects could get justice for violations of their rights that have been carried out by investigators. Another thing that can be done by the suspects to investigators who have violated their rights to make efforts to force and violence against the suspect is to report the investigator to the authorities, that the investigator who reportedly has committed the crime by committing violence against a suspect who can associated with Article 351 of the Criminal Code of the persecution that led to suspects suffering from both physical and spiritual. Obstacles encountered in providing legal protection is not yet the enactment of existing laws and regulations in as much as there are sociological does not apply in the community. In addition due to the attitude of the defendant itself that can not be invited to cooperate. Another thing that causes is still incomplete enforcement of the rights of the suspect because of the low level of professionalism officials investigator investigators and officials in performing their duties. Lack of existing facilities and infrastructure and the lack of funds to conduct investigations and inquiries also causes still somewhat difficult enforcement of the rights of suspects. There is still a lack of supervision and control by the time checks take place, thus making the investigator freely at will itself carry out checks according to the way in love